A study on torrefaction of spent coffee ground to improve its fuel properties. (15th June 2022) - Nepal, Rabin; Kim, Hyeok Jin; Poudel, Jeeban; Oh, Sea Cheon
Highlights: Holistic approach to obtaining the optimum torrefaction condition of spent coffee ground. The fuel properties of torrefied spent coffee grounds were studied using proximate, elemental, gas and FTIR analysis. Abstract: Excessive use of fossil fuels has contributed significantly to global warming and the impending energy crisis, necessitating the promotion and development of alternative energy sources to achieve green energy or energy neutrality. Converting waste biomass into energy has a significance impact in solid waste management. Spent coffee grounds (SCG) are the primary residue from the coffee industry generated during the coffee brewing process. This study, therefore, aims to improve the fuel properties of SCG via torrefaction and investigates the characteristics of torrefied products. A horizontal tubular reactor, at temperatures ranging from 250 °C to 350 °C at 20 °C intervals, and residence times ranging from 0 to 30 min with 10-min intervals, were utilized for torrefaction. The associated physical and chemical transformations in SCG torrefaction were investigated using proximate and ultimate analysis, gas composition, thermogravimetric and derivative analyses along with Fourier Transform Infrared Spectroscopy (FTIR). The mass and energy yields decreased while the higher heating value increased with the increase in torrefaction temperature. Additionally, the decrease in the oxygen content and increase in the fixed carbon content helped to improve the fuel properties of the SCG. A torrefaction temperature of 290 °C and a residence time of 10 min was found to be the optimal conditions for SCG torrefaction.